Novel tridentate nitrogen donor as ligand in copper catalyzed ATRP of methyl methacrylate - Mittal, A.; Sivaram, S. (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
A tridentate ligand, BPIEP: 2,6-bis[1-(2,6-diisopropyl phenylimino) ethyl] pyridine, having central pyridine unit and two peripheral imine coordination sites was effectively employed in controlled/''living'' radical polymerization of MXU at 90 degrees C in toluene as solvent, (CuBr)-Br-I as catalyst, and ethyl-2-bromoisobutyrate (EBiB) as initiator resulting in well-defined polymers with polydispersities M-W/M-n <= 1.23. The rate of polymerization follows first-order kinetics, k(app) = 3.4 x 10(-5) s(-1), indicating the presence of low radical concentration ([P*] <= 10(-8)) throughout the reaction. The polymerization rate attains a maximum at a ligand-to-metal ratio of 2:1 in toluene at 90 degrees C. The solvent concentration (v/v, with respect to monomer) has a significant effect on the polymerization kinetics. The polymerization is faster in polar solvents like, diphenylether, and anisole, as compared to toluene. Increasing the monomer concentration in toluene resulted in a better control of polymerization. The molecular weights (M-n,M-SEC) increased linearly with conversion and were found to be higher than predicted molecular (M-n,M-Cal). However, the polydispersity remained narrow, i.e., <= 1.23. The initiator efficiency at lower monomer concentration approaches a value of 0.7 in 110 min as compared to 0.5 in 330 min at higher monomer concentration. The aging of the copper salt complexed. with BPIEP had a beneficial effect and resulted in polymers with narrow polydispersitities and higher conversion. PMMA obtained at room temperature in toluene (33%, v/v) gave PDI of 1.22 (Mn = 8500) in 48 h whereas, at 50 degrees C the PDI is 1.18 (Ma = 10,300), which is achieved in 23 h. The plot of In kapp versus 1/T gave an apparent activation energy of polymerization as (Delta E-app(not equal)) 58.29 KJ/mol and enthalpy of equilibrium (Delta H-eq(0)) to 28.8 KJ/mol. Reverse ATRP of MMA was successfully performed using AIBN in bulk as well as solution. The controlled nature of the polymerization reaction was established through kinetic studies and chain extension experiments. (c) 2005 Wiley Periodicals, Inc.
Keywords: 2; 6-bis [1-(2; 6-diisopropyl phenylimino) ethyl] pyridine (BPIEP); Activation energy; apparent rate constant; Atom transfer radical polymerization (ATRP); diphenylether; ethyl-2-bromoisobutyrate (EBiB); methyl methacrylate; polydispersity index (PDI); Toluene